Drought protection from an in-lieu groundwater banking program - Kubit, Owen E., author; Moss, Richard M., author; Roldan, John P., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2007)
The framework is provided for a drought preparedness plan (Drought Plan) for the Orange Cove Irrigation District (District) located in the Central Valley of California. The Drought Plan will improve water supply reliability for the District, which needs a firm water supply to support permanent plantings that cover over 90 percent of the District. The District uses a combination of surface and groundwater and has surplus surface water in some years, but the local geology is not favorable for direct recharge using ponding basins. The District therefore investigated several options for drought protection including water purchases, out-of-District groundwater banking, and in-lieu groundwater recharge in their own service area. In-lieu groundwater recharge was found to be the most economical alternative and would be under the full control of the District. Under the program, some District growers would be sold surplus surface waters at reduced rates, and this would allow groundwater levels to rise and groundwater storage to increase. In dry years, these growers would meet most or all of their demands with groundwater, and would transfer their surface water to areas with low groundwater yields. Details of the program were developed with considerable input from local growers through a public outreach program. A pilot program was outlined with the intention of testing the feasibility of the program on a smaller scale. Other topics discussed include incentives for growers to participate, groundwater level monitoring, project benefits and impacts, and project economics. The California Department of Water Resources funded development of the program.
USCID fourth international conference
Not digitized by CSUL Digital Services.
Presented at the Role of irrigation and drainage in a sustainable future: USCID fourth international conference on irrigation and drainage on October 3-6, 2007 in Sacramento, California.